PENGGUNAAN MEDIA DIGITAL DAN TEKNOLOGI PENDIDIKAN DALAM PEMBELAJARAN, Frezy Paputungan, Sulastri Pua Age: PENGGUNAAN MEDIA DIGITAL DAN TEKNOLOGI PENDIDIKAN DALAM PEMBELAJARAN, Frezy Paputungan, Sulastri Pua Age - Frezy Paputungan; Sulastri Age (Jurnal Ilmu Pendidikan dan Budaya, 2023)
Digital content in the changing times in building a digital ecosystem is of course also supported by healthy internet behavior, these two things are important and cannot be separated. The internet has opened various information doors that contain various contents, both positive content and negative content. If we don't have provision in how to use it, the internet will become a scourge for its users. Therefore debriefing and creating positive content is important, providing continuous education to every user and content creator, so that they have good literacy in using digital technology, making the internet part of an effective and positive learning tool. Digital content will act like currency in a digital social education environment, various communications will be represented by playing or utilizing digital content. Of course, digital content delivery modes in the future will become easier, cheaper, faster and more varied as capacity (bandwidth) develops or increases, devices are more innovative, and it is also easy to get cloud-based applications and storage space. The expectations of the current generation will be different from previous generations, they will need the practice of sharing experiences through digital content including learning content, various digital communication media will become richer with knowledge sources and digital content. On the other hand, there are also many tools to support creative content creation in digital form and are adaptive to the needs of users and the needs of their media distribution. language boundaries, cultural boundaries, age limits and other boundaries.